NitroSynapsin therapy for a mouse MEF2C haploinsufficiency model of human autism. Issue 1 (December 2017) - Tu, Shichun; Akhtar, Mohd Waseem; Escorihuela, Rosa; Amador-Arjona, Alejandro; Swarup, Vivek; Parker, James; Zaremba, Jeffrey; Holland, Timothy; Bansal, Neha; Holohan, Daniel; Lopez, Kevin; Ryan, Scott; et al.
Abstract Transcription factor MEF2C regulates multiple genes linked to autism spectrum disorder (ASD), and human MEF2C haploinsufficiency results in ASD, intellectual disability, and epilepsy. However, molecular mechanisms underlyingMEF2C haploinsufficiency syndrome remain poorly understood. Here we report thatMef2c +/− (Mef2c -het) mice exhibit behavioral deficits resembling those of human patients. Gene expression analyses on brains from these mice show changes in genes associated with neurogenesis, synapse formation, and neuronal cell death. Accordingly, Mef2c- het mice exhibit decreased neurogenesis, enhanced neuronal apoptosis, and an increased ratio of excitatory to inhibitory (E/I) neurotransmission. Importantly, neurobehavioral deficits, E/I imbalance, and histological damage are all ameliorated by treatment with NitroSynapsin, a new dual-action compound related to the FDA-approved drug memantine, representing an uncompetitive/fast off-rate antagonist of NMDA-type glutamate receptors. These results suggest thatMEF2C haploinsufficiency leads to abnormal brain development, E/I imbalance, and neurobehavioral dysfunction, which may be mitigated by pharmacological intervention. Human MEF2C haploinsufficiency results in Autism Spectrum Disorder (ASD), but it is unclear if the same is true in mice. Here, the authors show thatMef2c +/− mice have behavioral defects and neuronal abnormalities similar to ASD, and symptoms can be ameliorated with the new drug, NitroSynapsin.